CATCHING INFLATION BY THE TAIL - Animal metaphoric imagery in the conceptualisation of INFLATION in English - Nadezda Silaski (Ibérica, Revista de la Asociación Europea de Lenguas para Fines Específicos, 2010)
ANIMAL metaphors are conventional in many languages and their metaphoricaluse is not limited only to human beings, non-physical domains may also be understood in terms of the assumed properties of animals. Set within the wider theoretical framework of Cognitive Theory of Metaphor, this paper deals with the conceptualisation of INFLATION as an ANIMAL in English. We focus on the INFLATION IS A FEROCIOUS ANIMAL metaphor, in which the most salient properties of wild animals as a source domain are mapped onto the abstract and complex target domain, INFLATION, producing various conceptual mappings, which refer to the ways wild animals move, look, sound, eat/are fed, attack and are controlled. We show how the INFLATION IS AFEROCIOUS ANIMAL metaphor functions within popular economic discourse, as well as how it structures our thinking about inflation, a dangerous phenomenon which poses a potential threat to every economy in the world.